Understanding consumers’ purchase intentions of single-use plastic products - Sun, Ying; He, Haonan (Frontiers in Psychology, 2023)
Human health and marine life are facing the hazards and threats of plastic waste. China is the world’s largest producer and consumer of disposable plastic products, thus pay more attention to the threats and challenges of single-use plastics products in China is urgent. This study aims to explore the intention to purchase single-use plastic products based on the theory of planned behavior. Data collection using self-reported questionnaires, and 402 valid questionnaires were obtained, thus analyzed using Amos 22.0 and SPSS 18.0 software. Results indicate that attitude, perceived behavioral control, normative social influence, informational social influence and positive anticipated emotion positively affects intention to purchase single-use plastic products. Meanwhile, positive anticipated emotion positively moderates the relationship between normative social influence and intention to purchase single-use plastic products, but negatively moderates the relationship between informational social influence and intention to purchase single-use plastic products. This research provides some theoretical and policy implications to help relevant agencies design targeted interventions to address environmental issues related to single-use plastic consumption.